PERAN LINGKUNGAN KELUARGA DALAM MOTIVASI MINAT BACA PADA SISWA MI NURUL YAQIN KOTA PROBOLINGGO - Hasan, Aqilul; Khosiah, Nur (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study shows the importance of active family involvement in creating a reading culture from an early age. The purpose of this study was to examine the role of the family environment in shaping and increasing the reading interest of fourth grade students at MI Nurul Yaqin, Probolinggo City. The focus of the study includes parental involvement in literacy activities, the availability of reading materials at home, and the creation of a literate atmosphere in the family environment. This study uses a descriptive qualitative method with data collection techniques in the form of observation, interviews, and documentation. The results of the study showed that students who come from families with good reading habits and consistent educational support have a higher interest in reading. This finding confirms that the active role of the family is very influential in fostering a culture of literacy from an early age.